Surgical considerations about the anterior syphon knee of the internal carotid artery - Murilo S. Meneses; Danielle Molinari; Marcia Fortes; Patricia Rangel; Tatiana Neves; Ari Pedroso; Ricardo Ramina (Arquivos de Neuro-Psiquiatria)
An anatomical study about the anterior knee of the intracavernous carotid artery is presented. Twenty cavernous sinuses (CS) were dissected in cadavers using microsurgical techniques. A fibrous ring around the internal carotid artery (ICA) at the CS roof was found in all specimens. This fibrous attachment could be dissected from the surrounding dura and a loose connective tissue could be demonstrated around the ICA. This anatomical finding makes possible the microsurgical approach to vascular lesions of this portion of the ICA, without opening the cavernous sinus.